A tradução pedagógica de textos multimodais como ferramenta de ensino de língua estrangeira: um estudo qualitativo do uso de tirinhas em sala de aula on-line - Vale, Paulo Igo Lima (2021)
Translation has long been banned from foreign language classes. However, this exclusion ignored its numerous benefits to studens. In recent years, however, translation has begun to find its place back to the language classroom and it is now taking a prominent place in different approaches implemented in foreign language teaching as an additional tool to facilitate language learning. Based on the principle that translation is useful for the development of communication skills, this research aims to investigate the use of pedagogical translation as a teaching tool for the acquisition of new words in a foreign language based on the comic strip genre in online classes. In order to achieve our research goal, we rely on studies on pedagogical translation (CORREA, 2014; LAVALT, 1985; TESSARO, 2012; SANDES; PEREIRA, 2017; SANTOS, 2014), and others. We also discuss the characteristics of the comic strip genre (VERGUEIRO, 2004; RAMOS, 2017), especially concerning the theories of multimodaly and intersemiotic translation (CARVALHO, 2016; DINIZ, 1999; KRESS, 2011; PLAZA, 2003), and its relation to vocabulary learning (LEWIS, 1993; NATION, 2001). We also address online education and all the challenges that this approach has brought during the COVID-19 pandemic period (ANTUNES NETO, 2020; ARRUDA, 2020; JOYE; MOREIRA; ROCHA, 2020; MAIA; MATTAR, 2008; TORI, 2010). The study consists of a qualitative action research in which we present a didactic sequence proposal (DS) focusing on translation activities of comic strips in online classrooms. The activities were developed with students of the ninth and the eighth grade of an elementary public school in Fortaleza. Our corpora consist of questionnaires and DSs developed at the beginning and at the end of the research. Thus, we realize that translation activities based on comic strips can be both relevant to the development of the students' lexicon and is a motivating element for their engagement in language learning.